PENGARUH KUALITAS KEHIDUPAN KERJA, PENGHARGAAN DAN EFIKASI DIRI TERHADAP EFEKTIVITAS MANAJERIAL KEPALA SMA SWASTA DI JAKARTA TIMUR - RAHMAWATI, DESI (PPs UNJ, 2015)
The objective of this causal research was to obtain information concerning the effect of quality of worklife, reward, and self efficacy on managerial effectiveness of the principals of private high school in east Jakarta. The research was conducted by using a survey method with path analysis in testing hypothesis. In this research, principals of private high school has been choosen as a unit analysis and 66 samples of principals were selected in random. The results of the research are as follows; (1) there is a direct positive effect of quality of worklife on managerial effectiveness, (2) there is a direct positive effect of reward on managerial effectiveness, (3) there is a direct positive effect of self efficacy on managerial effectiveness, (4) there is a direct positive effect of quality of worklife on self efficacy, (5) there is a direct positive effect of reward on self efficacy. Therefore, to improve managerial effectiveness, Private school foundations should gives more attention to the fulfillment of the needs of facilities and infrastructure in schools. Principals should more adaptive in response to the changes. School principals should be able to compensate for changes in education that is so dynamic and managing changes to improve the quality of school.